A review of the marine crab fisheries in the Turkish seas - Harlıoğlu, Muzaffer Mustafa; Farhadi, Ardavan; Ateş, Abdullah Suat (Sciendo, 2018)
The paper presents a review of the distribution of marine crabs (Brachyura) along the Turkish coast and the amount of economically important marine crabs harvested between 1967 and 2016. Previous records reported that Turkey had 102 brachyuran crab species, only five of them being economically important, but this review identifies two more species, Inachus phalangium and Ashtoret lunaris. The Aegean Sea has more crab species than the Mediterranean, the Black Sea and the Sea of Marmara. The most harvested species are Callinectes sapidus, Maja squinado, Eriphia verrucosa, Carcinus aestuarii and Portunus segnis, respectively. This review shows that there have been fluctuations in the harvest of marine crabs between years, the lowest being 5 tonnes in 2015 and the highest, 2116 tonnes in 1984. The information provided in this review provides a basis for potential profitable development of conservation and management strategies of marine crabs in Turkey. © The Author(s) 2018. Published by University of Zagreb, Faculty of Agriculture. All rights reserved.
Keywords: Brachyura; Decapoda; Distribution; Economy; Fisheries; Turkey